Transformation of Regulatory Efforts Land Tenure and Land Ownership in Indonesia - Dewi Marlina Putri, Sri; Reviandini, Titi; Puspasari, Mela (Veteran Law Review, 2025)
Land is one of the potential agrarian resources. Land can reflect a social status of person which increasingly the land that someone have, so status social in society is higher. This causes high inequality of land ownership in Indonesia with proven that the Gini index ratio is almost to 0,48. Several regulations have been issued to address the inequality of land ownership. The research focuses on the study of land tenure dan land ownership that has been regulates in Indonesia, regulation in the agrarian statue and job creation statue. This study uses a normative juridical approach with an emphasis in analysis on positive legal norm in laws and regulation. The result show that existing regulations have not answered the main problem of inequality land ownership and there are no comprehensive norms which restrictions of national quantitative land tenure and land ownership, so that has the potential to create a monopoly on land tenure. Therefore, The Government needs to reformulate the regulation of the control and ownership of agricultural and non-agricultural land for both individuals and legal entities.